Participant and Strategy Selection of Health QR Code Product Experience Design during the COVID-19 Pandemic in China: The Information Security Perspective - Zishun Su; Qiaoling Zou; Xinying Wu; Junnan Ye; Jianxin Cheng (Discrete Dynamics in Nature and Society)
Health QR code is an Internet product designed and developed by China to combat the COVID-19 pandemic. In order to build a public health and epidemic prevention barrier, the Chinese government’s health QR code product is a useful attempt to deal with epidemic prevention and control and social governance in the way of “Internet plus big data”. In the process of health QR code product design and development, we conduct a security analysis of information data and employ project management, product design, development and testing, online, and operational product experience design methods. User requirements and product definitions for the health QR code include management, design, development, and testing. The main participants of health QR code product experience design are divided into product manager, design and development team, and users. The relationships among the product manager, the design and development team, and users are established using the evolutionary game method. It is found that the cost of information security has an important influence on the choice of the user policy. Product managers, driven by benefits and values, may ignore the importance of information security when choosing the strategy for health QR code products, which will affect users' enthusiasm to use them to some extent and limit their use scenarios and application scope. Therefore, in order to achieve healthy user interaction and sustainable experience design of health QR code products, it is necessary to strengthen data security protection and reduce the cost of information interaction and sharing. Furthermore, on the basis of enhancing user viscosity and improving the usability of health QR code products, our research results show the further need for demand mining and version upgrading of health QR code products.